Proceedings of the 3rd Conference on Designing Interactive Systems: Processes, Practices, Methods, and Techniques 2000
DOI: 10.1145/347642.347799
|View full text |Cite
|
Sign up to set email alerts
|

A dimension space for the design of interactive systems within their physical environments

Abstract: This paper introduces a Dimension Space describing the entities making up richly interactive systems. The Dimension Space is intended to help designers understand both the physical and virtual entities from which their systems are built, and the tradeoffs involved in both the design of the entities themselves and of the combination of these entities in a physical space. Entities are described from the point of view of a person carrying out a task at a particular time, in terms of their attention received, role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Dimension space analysis is a related approach to system design that retains the goals of supporting design practice and facilitating communication [6]. Although dimension space analysis does not explicitly incorporate the QOC method of outlining the design space of a system, it preserves the notion of a system inhabiting a finite space within the space of all possible design options, and it sets up the dimensions of this space to correspond to various object properties.…”
Section: Dimension Space Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Dimension space analysis is a related approach to system design that retains the goals of supporting design practice and facilitating communication [6]. Although dimension space analysis does not explicitly incorporate the QOC method of outlining the design space of a system, it preserves the notion of a system inhabiting a finite space within the space of all possible design options, and it sets up the dimensions of this space to correspond to various object properties.…”
Section: Dimension Space Analysismentioning
confidence: 99%
“…The Dimension Space outlined by Graham [6] represents interactive systems on six axes. Each system component is plotted as a separate dimension space so that the system can be examined from several points of view.…”
Section: Dimension Space Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…the design of interactive systems within their physical environments. Graham et al (2000) describe a Dimension Space "intended to help designers understand both the physical and virtual entities from which their systems are built, and the tradeoffs involved in both the design of the entities themselves and of the combination of these entities in a physical space". This need for better studying and supporting the interaction designer's work is even more evident in the case of model-based tools (Paternò, 2005;Navarre et al, 2001;Vanderdonckt and Berquin, 1999), which are our main research focus.…”
Section: Studying and Supporting The Designer's Behaviormentioning
confidence: 99%
“…HCI researchers have found that system design requires a deep understanding of the user's tasks [11] and the user's physical context [12]. Scenarios of use [7] can be developed to show the broader context of diagram use.…”
Section: Existing Research Into User Interfacesmentioning
confidence: 99%